Post-conization pathological upgrading and outcomes of 466 patients with low-grade cervical intraepithelial neoplasia - Guo, Yulin; Cai, Hongning; Peng, Qiuzi; Wang, Ying; Li, Lu; Zou, Miao; Guo, Jinyue; Wang, Chaonan; Wu, Xufeng; Ma, Quanfu (Frontiers in Oncology, 2024)
IntroductionThe management of patients with low-grade cervical intraepithelial neoplasia (CIN1) remains controversial. We analyzed the pathological upgrading rates of patients with CIN1 undergoing conization, identifying influencing factors, and compared their outcomes to those of patients with CIN1 receiving follow-up only.MethodsThis retrospective study included 466 patients with CIN1 confirmed by histopathology and treated with conization. Postoperative pathological upgrading was determined and its influencing factors were identified. We also analyzed post-conization outcomes, examining the rate of persistent/recurrent CIN1 and its influencing factors, and comparing these results to those of patients receiving follow-up only.ResultsThe pathological upgrading rate of patients with CIN1 after conization was 21.03% (98/466), and the influencing factors were preoperative high-risk human papillomavirus (HR-HPV) infection and cytological results. The upgrading rates of HR-HPV positive and negative patients were 22.05% and 0.00%, respectively (χ2 = 5.03, P=0.03). The upgrading rate of patients with cytological results negative for intraepithelial lesion malignancy was 10.94%, while the upgrading rates of atypical squamous cells, cannot exclude high-grade lesion(ASC-H) and high-grade squamous intraepithelial lesion(HSIL) groups were 47.37% and 52.94%, respectively (χ2 = 22.7, P=0.03). Persistent/recurrent CIN1 rates in the conization group were 21.24%, 15.97%, and 6.67% at 6, 12, and 24 months, respectively, significantly lower than those in the follow-up only group. The CIN2 progression rate in the conization group (0.26%) during the 24-month follow-up period was also significantly lower than that in the follow-up only group (15.15%; χ2 = 51.68, P<0.01). The only factor influencing postoperative persistent/recurrent CIN1 was preoperative HR-HPV status. No patients who were HR-HPV negative preoperatively exhibited persistent/recurrent CIN1, compared with 25.55% of those who were HR-HPV positive preoperatively (χ2 = 4.40, P=0.04).DiscussionThe risk of progression to CIN2+ in the medium term is higher in patients with CIN1 receiving follow-up than in those undergoing conization. Doctors should refer to the guidelines but comprehensively consider age, fertility requirements, preoperative HR-HPV and cytological results, follow-up conditions, and other factors to select the most appropriate treatment strategy for patients with CIN1.